Socioeconomic Outcome and Quality of Life in Adults after Status Epilepticus: A Multicenter, Longitudinal, Matched Case–Control Analysis from Germany - Kortland, Lena-Marie; Knake, Susanne; von Podewils, Felix; Rosenow, Felix; Strzelczyk, Adam (Frontiers in Neurology, 2017)
BACKGROUND: There is a lack of data concerning socioeconomic outcome and quality of life (QoL) in patients after status epilepticus (SE) in Germany. PATIENTS AND METHODS: Adult patients treated between 2011 and 2015 due to SE at the university hospitals in Frankfurt, Greifswald and Marburg were asked to fill out a questionnaire regarding long-term outcome of at least three months after discharge. The SE cohort consisted of 25.9% patients with an acute symptomatic, 42% with a remote symptomatic and previous epilepsy, 22.2% with a new onset remote symptomatic, and 9.9% with other or unknown etiology. A matched case-control analysis was applied for comparison to Ppatients with drug-refractory epilepsy and in seizure remission, both not previously affected by SE. RESULTS: A total of 81 patients (mean age: 58.7±18.0 years; 58% female) participated. A non-refractory course was present in 59.3%, while 27.2% had a refractory SE (RSE) and 13.6% a super-refractory SE (SRSE). Before admission, a favorable modified Rankin Scale (mRS) of 0-3 was found in 82.7% (67/81), deteriorating to 38.3% (31/81) p=0.003) at discharge. The majority returned home (51.9% [42/81]), 32.1% entered a rehabilitation facility, while 12.3% were transferred to a nursing home and 3.7% to another hospital. The overall mRS at follow-up did not change; 61.8% (45/74) reached an mRS of 0-3. In RSE and SRSE the proportion with a favorable mRS increased from 45.5% at discharge to 70% at follow-up, while QoL was comparable to a non-refractory course of SE. Matched epilepsy controls in seizure remission were treated with a lower mean number of anticonvulsants (1.3 ± 0.7) as compared to controls with drug-refractory epilepsy (1.9 ± 0.8; p<0.001) or SE (1.9 ± 1.1; p<0.001). A major depression was found in 32.8% of patients with SE and in 36.8% of drug-refractory epilepsy, but only in 20.3% of patients in seizure remission. QoL was reduced in all categories (QOLIE-31) in SE patients in comparison to patients in seizure remission, but was comparable to patients with drug-refractory epilepsy. DISCUSSION: Patients after SE show substantial impairments in their QoL and daily life activities. However, in the long-term patients with RSE and SRSE